Analisis Strategi Words of Mouth melalui Booklet pada Strategi Pemasaran Jasa Wedding Organizer Menggunakan Metode SWOT (Strength, Weakness, Threat, Opportunity) : Studi Kasus pada Kabio Wedding - Tamba, Devina Ulima Nathania; Afriani, Audina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Marriage is considered sacred and is only done once in a lifetime which makes the bride and groom and their families have diverse and complex needs and desires for the event, they tend to need help from wedding organizer services because they feel they can help the running of the wedding event. With this high market interest, the level of competition for wedding organizer services is even higher and they are competing to secure their position. This study aims to find out how to apply the Words of Mouth strategy concept through the booklet that is applied by Kabio Wedding in conducting marketing using the SWOT (Strength, Weakness, Threat, Opportunity) method. This research was conducted at Kabio Wedding Wedding Organizer Services using a qualitative descriptive method by presenting data and drawing conclusions. The type of data in this study uses primary data obtained directly from interviews with the owner of Kabio Wedding and direct field observations. Secondary data obtained from related journals and e-books. The results of the study show that the implementation of the word of mouth strategy is effective and efficient for Kabio Wedding, but it still needs attention and improvement because it is easily imitated by competitors and can only pursue the target market of parents.